IDENTIFIKASI DAN INVENTARISASI IKAN-IKAN DARI WADUK PLTA KOTO PANJANG KABUPATEN KAMPAR, RIAU - Sampe Harahap; Syafriadiman '; Erian Hur (Berkala Perikanan Terubuk, 2010)
This research was conducted on October to Desember 2009 at PLTAKoto Panjang reservoir an Fisheries Biology Laboratory, Fisheries and MarineScience Faculty University of Riau. The objective of this research was toindentify, find out varieties and economics value of fish occured at the reservoir.The method applied in this research was survey method by applying 7 stations forfish collection. Sample identification generated 44 varieties, these sorts included 6Ordos, 17 Familyes and 30 Genus. From 44 varietes collected could be identifiedthat 30 ot them were ornamental fishes, 33 kinds were consumed fishes and 7kinds were aquaculture fishes. These fishes may occur in the dam because theyescape from the cages or because the PLN distributed the fishes in the dam by2001 and now they reproduced.